2017
DOI: 10.3390/v9070159
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Organosulfur Compounds Reduce Inflammation and Oxidative Stress during Dengue Virus Infection

Abstract: Dengue virus (DENV) is a mosquito-borne flavivirus that causes significant global human disease and mortality. One approach to develop treatments for DENV infection and the prevention of severe disease is through investigation of natural medicines. Inflammation plays both beneficial and harmful roles during DENV infection. Studies have proposed that the oxidative stress response may be one mechanism responsible for triggering inflammation during DENV infection. Thus, blocking the oxidative stress response coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…The presence of orgasulfur compounds in other species motivated a wide cluster of studies mainly focused on health promoting effects [46,47,48,49]. These findings and the results presented in the present conference paper justify more pharmaceutical and nutraceutical researches as a new trend of investigation for M. alliacea.…”
Section: Discussionsupporting
confidence: 67%
“…The presence of orgasulfur compounds in other species motivated a wide cluster of studies mainly focused on health promoting effects [46,47,48,49]. These findings and the results presented in the present conference paper justify more pharmaceutical and nutraceutical researches as a new trend of investigation for M. alliacea.…”
Section: Discussionsupporting
confidence: 67%
“…Several organosulfur compounds of garlic have been shown to exert multiple pharmacological activities (32)(33)(34)(35)(36)(37)(38), and studies have demonstrated that aqueous garlic extract has antioxidant properties (39,40). It is well-known and well-published that garlic extract possessed the strong antioxidant activities in vitro and in vivo (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Flaviviruses are arboviruses transmitted to vertebrate hosts by a vector arthropod (ticks and mosquitoes). Some flaviviruses, such as DENV, YFV, WNV, SLEV, Japanese encephalitis virus (JEV), or encephalitis virus transmitted by ticks (TBEV), cause diseases in humans, and the signs can vary from a nonspecific febrile syndrome, encephalitis, hemorrhagic fever, and death (Calisher and Gould, 2003;Hall et al, 2017;Feitoza et al, 2017). The DENV is mainly transmitted by female mosquitoes of the genus A. aegypti and A. albopictus, distributed in all tropical and subtropical countries, both species considered invasive (Rey and Lounibo, 2015).…”
Section: Generalities Of Flavivirusmentioning
confidence: 99%